Reactive oxygen species-targeted therapeutic interventions for atrial fibrillation - Sovari, Ali A.; Dudley, Jr., Samuel C. (Frontiers in Physiology, 2012)
Atrial fibrillation (AF) is the most common arrhythmia that requires medical attention and its incidence is increasing. Current ion channel blockade therapies and catheter ablation have significant limitations in treatment of AF mainly because they do not address the underlying pathophysiology of the disease. Oxidative stress has been implicated as a major underlying pathology that promotes AF; however, conventional antioxidants have not shown impressive therapeutic effects. A more careful design of antioxidant therapies and better selection of patients likely are required to treat effectively AF with antioxidant agents. Current evidence suggest inhibition of prominent cardiac sources of reactive oxygen species (ROS) such as nicotinamide adenine dinucleotide phosphate oxidase and targeting subcellular compartments with the highest levels of ROS may prove to be effective therapies for AF. Increased serum markers of oxidative stress may be an important guide in selecting the AF patients who will most likely respond to antioxidant therapy.